2012
DOI: 10.3390/ijms130912046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Characterization of Porcine Reproductive and Respiratory Syndrome Virus Isolates in Romania, Based on Phylogenetic Analysis

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a disease produced by the (PRRS) virus, characterized by endemic evolution in the majority of countries, which remains in actuality being a permanent threat to health and economic free farms, as well as for those infected. The aim of this study was to evaluate the genetic diversity of Romanian PRRSV isolates from the four most important pig farms in Romania by comparing the nucleotide sequences obtained for ORF5 and ORF7 with a wide range of sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The authors also suggested multiple introductions of PRRS in their country 26 . A recent study involving relatively low number of sequences revealed that Romanian PRRSV sequences are clustered in three groups within Subtype 1 27 . Another recent paper describing the analysis of PRRSV strains from Slovakia, Czech Republic and a few from Austria revealed that Slovakian strains were clustered into three phylogenetic branches, whereas the Czech and the Austrian ones were mostly forming single nodes on the Subtype 1 part of the tree 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors also suggested multiple introductions of PRRS in their country 26 . A recent study involving relatively low number of sequences revealed that Romanian PRRSV sequences are clustered in three groups within Subtype 1 27 . Another recent paper describing the analysis of PRRSV strains from Slovakia, Czech Republic and a few from Austria revealed that Slovakian strains were clustered into three phylogenetic branches, whereas the Czech and the Austrian ones were mostly forming single nodes on the Subtype 1 part of the tree 28 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, fluorescent quantitative PCR is primarily used to differentiate various viruses causing reproductive disorders, such as distinguishing PRRSV from African swine fever virus, classical swine fever virus, porcine parvovirus, and pseudorabies virus [ 25 , 26 , 27 ]. Some detection methods can differentiate classical strain from highly pathogenic PRRSV strains [ 28 ], while other detection methods can distinguish between the two genotypes PRRSV1 and PRRSV2 [ 29 , 30 ]. In this study, we developed a multiple real-time PCR method for the detection and identification of the four subtypes of PRRSV strains that exist in China.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we performed PCR analysis using specific primers used for genotyping (Gallardo, 2009). The DNA sequencing reactions were performed as described previously (Zaulet, 2012). Briefly, the reaction products were purified using Wizard® PCR Preps DNA Purification System (Promega, Madison, WI, USA), and the concentration and purity of the products were evaluated by spectrophotometry (Eppendorf BioPhotometer, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%